Pengaruh Problem Based Learning Berbantuan Video terhadap Motivasi, Berpikir Kritis, dan Hasil Belajar IPS Siswa Kelas V SD - Muhammad Kalkautsar; Sugiharto Sugiharto; Sri Yunita; Noni Rozaini; Hidayat Hidayat; Winara Winara (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2026)
Improving learning motivation, critical thinking, and Social Studies achievement remains a major concern in elementary education, particularly in efforts to implement student-centered learning. This study investigated the effectiveness of Problem-Based Learning (PBL) integrated with instructional videos in enhancing these three learning outcomes among fifth-grade students. A quantitative quasi-experimental approach employing a non-equivalent control group design was adopted. The participants comprised 56 students, including 27 in the experimental group and 29 in the control group. Data were obtained through a learning motivation questionnaire, a critical thinking test, and a Social Studies achievement test, all of which demonstrated acceptable validity and reliability. Statistical analysis was conducted using Multivariate Analysis of Variance (MANOVA) after the assumptions of normality, homogeneity of variance, and homogeneity of covariance matrices had been satisfied. The findings indicated that students exposed to PBL supported by instructional videos outperformed those receiving conventional instruction across all measured variables (p < 0.05). The intervention explained 72.2% of the variance in learning motivation, 63.2% in critical thinking skills, and 74.0% in Social Studies achievement. The combination of authentic video-based problem presentation and collaborative inquiry encouraged students to investigate, discuss, and reflect more actively, leading to deeper learning experiences. These results provide empirical support for constructivist learning and the Cognitive Theory of Multimedia Learning, suggesting that integrating PBL with instructional videos represents an effective instructional approach for strengthening Social Studies learning and promoting twenty-first-century competencies in elementary schools.